Polyetheretherketone (PEEK) in Dental Implantology: A Systematic Review - Jahangiri, Maryam; Bakhtiari, Fatemeh; Shayegh, Sayed Shojaedin (Journal of Dental School, 2025)
Objective(s): Polyetheretherketone (PEEK) is a thermoplastic, semi-crystalline, aromatic polymer known for its excellent physical, mechanical, and electrical properties. This review has explored PEEK's properties and its diverse applications in the field of implantology. Methods: This systematic review was conducted based on the PRISMA guideline. All articles up to 2025 were searched in the PubMed, Google Scholar, Scopus, Springer Link, Science Direct, and Wiley databases using the relevant keywords. Among 170 relevant articles, the abstracts of 49 articles with the highest relevance to the topic were studied, and 25 articles with the highest relevance were selected and reviewed. Results: This study categorized the diverse applications of PEEK in implantology as follows: Implant fixtures, Temporary abutments, Permanent abutments, Scan bodies, Temporary implant prostheses, and Healing abutments. While numerous studies suggest that PEEK represents the future of dental materials science, further clinical research is warranted. Conclusion: The use of PEEK fixtures can prevent stress shielding due to its closer elastic modulus to the surrounding bone. However, the use of PEEK as an implant fixture faces challenges due to low osseointegration, and the use of surface coating is recommended. The probability of gaps in the abutment and implant margin in PEEK is higher than in titanium. Screw loosening in PEEK abutments is twice that of titanium types. But PEEK can be a good alternative for temporary abutments. Plaque accumulation to coarse PEEK particles is higher and is not recommended as a healing abutment. Due to the lack of light reflection, some believe that the PEEK scan body is more accurate than titanium types; however, studies have shown the opposite. Because PEEK is more flexible than titanium and moves during torque, it reduces the accuracy of the final scan.